THE INFLUENCE OF RETURN ON ASSET, CURRENT RATIO, TOTAL ASSET TRUNOVER ON STOCK RETURN THROUGH COMPANY VALUE AS A MODERATING VARIABLE IN CONSUMPTION GOODS INDUSTRIAL SECTOR COMPANIES LISTED ON THE BEI ​​FOR THE 2018-2022 PERIOD - Mega, Ajeng; Novi Susyani (OIKOS: Jurnal Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2024)
The aim of this research is to determine the impact of return on assets, current ratio and total asset turnover on stock returns using firm value as a moderating variable in the consumer goods industry sector. This research is quantitative research using secondary data sources in data collection. The data sampling method used a purposive sampling technique, namely 20 companies in the consumer goods industry over a period of 5 years. Data analysis was carried out using MRA analysis. This research finds that return on assets and total asset turnover have a positive impact on stock returns, while current ratio has no impact on stock returns. This research also shows that company value does not affect return on assets, current ratio and total stock return turnover.